Identification and antibiotic resistance of gram-negative bacteria isolated from Iloilo River. - Del Rosario, Louise Cecille S.
The Iloilo River is a source of sustenance and livelihood to some residents of Iloilo City, Philippines (Hechanova 2010). Species of Gram-negative bacteria were previously isolated from the river and antibiotic resistance patterns were described. The river is contaminated with a diversity of antibiotic resistant species. Putative Salmonella isolates by Araneta et. al. (2009) were used in this study. The API 20E and Bergey's Manual of Systematic Bacteriology were used to confirm the identity of 45 isolates. The results revealed that 91 percent (41/45) were Proteus mirabilis, 7 percent (3/45) were Citrobacter freundii, and 2 percent (1/45) were Salmonella sp. The Kirby-Bauer method of antibiotic susceptibility testing was used to identify the efficacy of the antibiotic, the antibiotic resitance patterns (ARP), and the occurrence of multiple antibiotic resistance (MAP) patterns of each species. Ciprofloxacin was the most effective antibiotic while doxycycline, tetracycline and erythromicin were the most ineffective. The tetracycline group, including tetracycline and erythromycin were the most ineffective. The tetracycline group, including tetracycline and doxycyline has been known to be highly effective against Gram-negative bacteria, but showed contrasting results. Increased antibiotic resistance is suspected. Gentamicin, and cefotaxime were not effective for Salmonella sp. and were only slightly effective for the other bacteria, these antibiotics are not ideal in treating Gram-negative bacteria as there was variable results. All species were resistant to multiple antibiotics. Salmonella sp. exhibited occurrence of MAR. protocols that respond to the threat of Gram-negative bacteria in the river should be formulated together with corresponding monitoring procedures for the prevention of their antibiotic resistance.